KONSEP KAFA’AH DALAM ISLAM: SUATU PENERAPAN DALAM PERNIKAHAN DITINJAU DARI MASLAHAH MURSALAH - Misbah Mrd; Sawaluddin Siregar; Nur Aminah Nst (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Kafa'ah has the meaning of balance or similarity between husband and wife both in terms of position (hasab), religion (din), descent (nasab) and physique. This study aims to examine the realization of a harmonious family with equal rights for married couples. The problem that will be studied is whether the concept of kafa'ah in marriage is good or vice versa (bad) by using maslahah mursalah as the analysis knife. The method used in this research is qualitative descriptive research with the type of library research. references, journals and other print media. The results of the study indicate that the concept of kafa'ah in marriage has benefits for achieving the goal of the marriage, namely achieving a sakinah, mawaddah and warohmah family. A peaceful family can be achieved with the efforts of each partner in building their household.